ANALISIS PRESTASI KERJA KARYAWAN DI PT. INDO PRIMA NUSANTARA MEDAN - RINA FRISKA B SIAHAAN; JESSIE SUSANA; WENY .; WILINNY .; WILLIAM VINCENT (JURNAL ILMIAH SIMANTEK, 2019)
Job performance is the result of work obtained by someone when completing work that is charged to him. work performanceappraisal is a process for evaluating employee work results for their work. The benefits of performance appraisal (workperformance) are: as input for leaders to help and direct employees to improve their performance in the future and to carryout improvements and improvements in human resource management activities. There are two factors that affect workperformance, namely: individual factors consisting of effort (abilities), abilities (abilities), role / task perception, andenvironmental factors consisting of physical conditions, equipment, time, material, education, supervision, organizationaldesign, training, good luck. The informants studied were employees at PT. Indo Prima Nusantara Medan. The researchmethod used is a qualitative method where the data obtained is based on interviews with data sources used are primarydata. The formulation of the problem in this study, "How the Employees' Job Performance at PT. Indo Prima NusantaraMedan? The purpose to be achieved in this study is to analyze and find out the Employee Job Performance at PT. IndoPrima Nusantara Medan. In this study we can see in the background the problem of employee work performance at PT. IndoPrima Nusantara Medan is very low and not in line with company expectations. This happens because employees alwayspostpone work so that the work cannot be completed in accordance with deadlines set by their superiors. From the researchresults obtained by researchers there are several shortcomings of the company for employee work performance. The resultsof these studies can be seen from the results of interviews that can. Therefore, researchers provide some advice in thisstudy for the company with the aim of improving employee performance in the company.